Nodular hidradenoma: A rare tumor in children - Sathe, Pragati A; Baste, Balaji D (Indian Journal of Child Health, 2018)
Hidradenomas are the benign cutaneous tumors of sweat gland origin, with the clear cell type constituting the most frequent histologic variety. Usually, they are diagnosed in the elderly population, the peak incidence being the fifth to sixth decade. Very few cases of hidradenoma have been documented in children in their first decade of life. Here, we present a rare and interesting case of a 10-year-old boy who presented with swelling on the anterior aspect of the neck, since birth. The histological findings were consistent with the diagnosis of nodular hidradenoma.